Pengaruh model discovery- inquiry learning terhadap kemampuan literasi sains pada materi gaya gravitasi bumi kelas IV Sekolah Dasar - Khairi Wulandari; Peduk Rintayati (Universitas Sebelas Maret, 2025)
The purpose of this study is to investigate how the science literacy abilities of fourth-grade elementary school pupils in Gugus III, Banjarsari Sub-district, Surakarta, are impacted by the learning model of inquiry and discovery. The experimental quantitative approach was applied in this study. Data was gathered using essay tests, and the Independent Sample t-test and N-Gain test were utilized for analysis. The results indicated a significant difference between the experimental group and the control group, with a significance value (2-tailed) of 0.000 <0.05. The control class's N-Gain value was 0.01 (low category), but the experimental class's was 0.44 (middle category). Accordingly, this study shows that the discovery-inquiry learning approach promotes the development of 21st-century skills, especially scientific literacy, and is successful in raising scientific literacy in elementary schools.